2020
DOI: 10.1039/d0ta03087b
|View full text |Cite
|
Sign up to set email alerts
|

The rational and effective design of nonfullerene acceptors guided by a semi-empirical model for an organic solar cell with an efficiency over 15%

Abstract: Guided by a semi-empirical model, two small-molecule acceptors were rationally designed and an impressive PCE of 15.05% was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 58 publications
2
52
0
1
Order By: Relevance
“…The V eff is the difference between the bias and the corresponding voltage under J ph = 0 condition. [ 31–34 ] The J ph of optimal ternary OPVs can arrive into saturated states at a relatively low V eff of ≈0.3 V, suggesting the efficient charge transport and collection in the ternary active layers, which can be further confirmed from the relatively large FF of 78.26%. [ 35 ] Under a relatively large V eff of ≈0.5 V, the values of J ph of BTP‐BO‐4F‐based binary and Y6‐1O‐based binary OPVs will come into saturated states, suggesting the insufficient charge transport in the two binary active layers.…”
Section: Resultsmentioning
confidence: 94%
“…The V eff is the difference between the bias and the corresponding voltage under J ph = 0 condition. [ 31–34 ] The J ph of optimal ternary OPVs can arrive into saturated states at a relatively low V eff of ≈0.3 V, suggesting the efficient charge transport and collection in the ternary active layers, which can be further confirmed from the relatively large FF of 78.26%. [ 35 ] Under a relatively large V eff of ≈0.5 V, the values of J ph of BTP‐BO‐4F‐based binary and Y6‐1O‐based binary OPVs will come into saturated states, suggesting the insufficient charge transport in the two binary active layers.…”
Section: Resultsmentioning
confidence: 94%
“…[52] In 2020, Wan et al designed an oxygencontaining ADA acceptor FO-2F. [53] Solar cells based on FO-2F and a polymer donor PM6 gave an impressive PCE of 15.05%. In 2018, Jen et al reported a nitrogen-containing acceptor SN6IC-4F.…”
Section: Small Molecule Nfas 2017-2020mentioning
confidence: 99%
“…designed an oxygen‐containing ADA acceptor FO‐2F. [ 53 ] Solar cells based on FO‐2F and a polymer donor PM6 gave an impressive PCE of 15.05%. In 2018, Jen et al.…”
Section: Molecular Design For Nfa Materials: Review and Perspectivementioning
confidence: 99%
“…之后, 他们 [73] [77] 采用"碳氧 桥"取代"碳桥"的策略设计了 CO i 8DFIC, 与 PTB7-Th 共混的器件效率达到 12.16%, J SC 高达 26.12 mA•cm -2 . 2020 年, 陈永胜等 [78] [85] . 一方面, 此类分子更倾向于醌式共振结构, 从 而在保持较深能级的情况下实现更窄的带隙, 获得更高 的 J SC ; 另一方面, 基于此类材料的活性层电致发光效 率较高, 可以有效减少器件的电压损失.…”
Section: 稠环电子受体unclassified